Antarctic Relic Microbial Mat Community Revealed by Metagenomics and Metatranscriptomics - Zaikova, Elena; Goerlitz, David S.; Tighe, Scott W.; Wagner, Nicole Y.; Bai, Yu; Hall, Brenda L.; Bevilacqua, Julie G.; Weng, Margaret M.; Samuels-Fair, Maya D.; Johnson, Sarah Stewart (Frontiers in Ecology and Evolution, 2019)
Buried upslope from the modern lakes in the McMurdo Dry Valleys of Antarctica are relict lake deposits embedded in valley walls. Within these relict deposits, ancient microbial mats, or paleomats, have been preserved under extremely arid and cold conditions since the receding of larger paleolakes thousands of years ago and now serve as a sheltered niche for microbes in a highly challenging oligotrophic environment. To explore whether paleomats could be repositories for ancient lake cells or were later colonized by soil microbes, determine what types of metabolic pathways might be present, analyze potential gene expression, and explore whether the cells are in a vegetative or dormant state, we collected paleomat samples from ancient lake facies on the northern slopes of Lake Vanda in Wright Valley in December 2016. Using a gentle lysis technique optimized to preserve longer molecules, combined with a polyenzymatic treatment to maximize yields from different cell types, we isolated high-molecular weight DNA and RNA from ancient paleomat samples. Community composition analysis suggests that the paleomat community may retain a population of indigenous mat cells that may flourish once more favorable conditions are met. In addition to harboring a diverse microbial community, paleomats appear to host heterotrophs in surrounding soils utilizing the deposits as a carbon source. Whole genome long-read PacBio sequencing of native DNA and Illumina metagenomic sequencing of size-sorted DNA (>2,500 nt) indicated possible cell viability, with mat community composed of bacterial taxa. Metagenome assemblies identified genes with predicted roles in nitrogen cycling and complex carbohydrate degradation, and we identified key metabolic pathways such as stress response, DNA repair, and sporulation. Metatranscriptomic data revealed that the most abundant transcripts code for products involved in genetic information processing pathways, particularly translation, DNA replication, and DNA repair. Our results lend new insight into the functional ecology of paleomat deposits, with implications for our understanding of cell biology, Antarctic microbiology and biogeography, and the limits of life in extremely harsh environments.